Culinary in Islamic-Javanese Cultural Heritage from a Chemistry Perspective - Zamhari, Muhammad (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2023)
Food plays a significant role in the religious rituals of Java, specifically within the realm of Islam, where special foods are prepared and consumed during religious ceremonies and celebrations, imbuing spiritual practices with a unique cultural essence. Understanding the chemistry behind these foods is essential for comprehending their health benefits and their embodiment of noble values within Javanese and Islamic cultures. This article seeks to delve into the chemistry of various cultural heritage foods from an Islamic-Javanese standpoint. To achieve this, a thorough literature review was conducted, focusing on culinary practices embedded within the Islamic-Javanese cultural heritage and exploring the corresponding chemical explanations. The research employed a systematic and meticulous search across academic databases, online libraries, and search engines to gather a broad range of perspectives, theories, and empirical evidence. Food, as a reflection of culture, serves both practical and symbolic roles within a particular cultural community. It serves as a manifestation of the values, traditions, and identity of the cultural group, while also meeting the physiological needs of individuals by providing essential nutrients and energy. Beyond mere sustenance, food holds utilitarian value by ensuring survival and promoting overall well-being. By delving into the chemistry of these cultural heritage foods, this article aims to shed light on their significance within the Islamic-Javanese context, uncovering the intricate interplay between chemistry, culture, and spirituality.